Zinc sulfate improves insulin resistance, oxidative stress and apoptosis in liver tissues of PCOS rats through the NF-κB pathway - Kang, Yi-fan; Zhao, Jia-yi; Liu, Jian-rong (Frontiers in Endocrinology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is primarily characterized by insulin resistance, which leads to increased hepatic glucose production and impaired insulin-mediated glucose disposal. Pathologically, this condition manifests as elevated liver cell apoptosis and reduced lipid transport capacity, further exacerbating insulin resistance. Liver cell apoptosis and mitochondrial dysfunction are key pathological features of PCOS-associated liver diseases, contributing significantly to the progression of PCOS. Although zinc sulfate is recognized for its antioxidant properties, its efficacy in ameliorating PCOS-related liver damage remains unclear.MethodsFemale Sprague-Dawley rats were induced with PCOS and non-alcoholic fatty liver disease (NAFLD) through a high-fat diet and letrozole administration over 28 days. Subsequently, the model rats received zinc sulfate treatment via gavage once daily for an additional 21 days. Serum hormone levels and biochemical markers were assessed using ELISA and enzymatic assays. Histological examination of ovarian and liver tissues was performed using hematoxylin and eosin (HE) staining, while hepatic lipid accumulation was evaluated by Oil Red O staining. Transmission electron microscopy was employed to examine liver cell ultrastructure, and TUNEL staining was used to assess hepatocellular apoptosis. Transcriptome sequencing was conducted on liver tissues to identify key genes and pathways, which were further validated by Western blotting and immunohistochemistry.ResultsInitial blood sampling revealed decreased serum zinc concentration in the PCOS group, alongside elevated levels of testosterone (T), luteinizing hormone (LH), alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglycerides (TG), total cholesterol (TC), blood glucose, fasting insulin, and oral glucose tolerance test (OGTT) values. However, the levels of serum estrogen (E2) and follicle-stimulating hormone (FSH) in the PCOS group were significantly decreased. Markers of oxidative stress, including malondialdehyde (MDA), superoxide dismutase (SOD), glutathione disulfide/glutathione ratio (GSSG/GSH), glutathione peroxidase (GSH-PX), and catalase (CAT), were also increased. Zinc sulfate treatment effectively improved all these parameters. HE and Oil Red O staining confirmed that zinc sulfate mitigated high-fat diet and letrozole-induced fatty liver. Furthermore, zinc sulfate alleviated severe hepatocellular apoptosis and mitochondrial damage observed in PCOS rats. Transcriptomic analysis indicated that zinc sulfate primarily mitigated PCOS-related liver damage via the cholesterol synthesis pathway, and experimental validation demonstrated that zinc sulfate inhibited oxidative stress and apoptosis in liver cells through the NF-κB pathway.ConclusionOur study demonstrates that zinc sulfate ameliorates liver oxidative stress and apoptosis in PCOS by modulating the NF-κB pathway, offering a novel therapeutic approach for managing PCOS-associated liver diseases.